2021
DOI: 10.3389/fmars.2021.653502
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Exposure of the Macaronesia Islands (NE Atlantic) to Marine Plastic Pollution

Abstract: The constant increase of marine plastic pollution poses an unprecedented risk to oceanic islands, which become increasingly exposed to a hazard of which they have very little control. Located in the Northeast Atlantic Ocean, the Macaronesia is comprised by the Azores, Madeira, Canary Islands, and Cabo Verde. Although past studies suggest that most plastic items collected on these islands are from offshore regions, their actual sources remain unclear to present date. As such, we focus on the characterization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 139 publications
(291 reference statements)
0
14
0
Order By: Relevance
“…Madeira Island is located on the external range of the North Atlantic Subtropical Gyre, an area of convergence where plastic debris is known to accumulate (Cozar et al, 2014). Through a modeling study, Cardoso and Caldeira (2021) found that Madeira Archipelago is significantly vulnerable to marine litter originating from distant sources. Litter particles, predominantly coming from the west coast of North America, are drifted by southward currents to Madeira (Gulf stream, Azores Current, Portugal, and Canary currents), mainly intercepting the north side of the island.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Madeira Island is located on the external range of the North Atlantic Subtropical Gyre, an area of convergence where plastic debris is known to accumulate (Cozar et al, 2014). Through a modeling study, Cardoso and Caldeira (2021) found that Madeira Archipelago is significantly vulnerable to marine litter originating from distant sources. Litter particles, predominantly coming from the west coast of North America, are drifted by southward currents to Madeira (Gulf stream, Azores Current, Portugal, and Canary currents), mainly intercepting the north side of the island.…”
Section: Discussionmentioning
confidence: 99%
“…A correlation between the monthly average precipitation and the microplastic abundance was not found in the present study, but a significant positive correlation was found between precipitation and zooplankton abundance. In comparison with estuarine or coastal environments, it can be expected that particles accumulation and dispersion in waters surrounding oceanic islands are more heavily subjected to physical oceanographic processes such as currents and winds, respect of surface run-off due to local meteorological events (Gove et al, 2016;Cardoso and Caldeira, 2021;Rosa et al, 2022). However, recent findings highlighted the underestimated impact of surface run-off episodes on suspended particulate matter and Chla concentration in waters surroundings Madeira Island (Rosa et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Turrell, 2020b), beaching is often parameterised by explicitly removing particles based on criteria, such as particles entering a land cell due to Stokes drift, wind and/or numerical error (e.g. Zhang et al, 2020;Cardoso and Caldeira, 2021), particle stagnation (e.g. Seo and Park, 2020;Bosi et al, 2021), or as a stochastic process associated with some probability (e.g.…”
Section: Particle Sinking and Beachingmentioning
confidence: 99%